Educação ambiental na gestão da coleta seletiva domiciliar no município de Lavras – MG: uma análise a partir do PGIRS municipal - Salgado, Juliano Jorge de Freitas (2021)
Solid waste has become a global problem, which directly and indirectly affects most communities, both rural and urban. The rampant consumption of products, the deficient management of their production chain by government agencies, the lack of public awareness and the lack of public incentive to reuse and regularly dispose of waste have become imperatives for the great socio-environmental problems to be faced in the 21st century. It is only through educational activities that all segments of civil society will be able to understand and act in a sustainable way towards them. These activities must be carried out by the government in partnership with all segments of civil society. Therefore, this study aims to analyze and discuss the approach to environmental education in the Integrated Solid Waste Management Plan of the municipality of Lavras (PGIRS) and its related documents as to its relevance in the selective collection of solid household waste. As well as in the understanding and development of actions by the managers responsible for the actions of environmental education in the municipality. The research was developed in an exploratory and descriptive manner with a qualitative approach, being carried out in two stages. The first stage consisted of bibliographical and documentary analysis and the second in the application of questionnaires together with ACAMAR, Lavras Municipality and CONSANE. As a result, it became evident that the municipality has solid waste management plans (PMSB and PGIRS) and the environmental education program is coordinated by the City Hall and CONSANE respectively. It was verified that ACAMAR works through a partnership with the City Hall promoting environmental education activities, with the delivery of pamphlets, and the collection of recyclables at home. It was observed, in PGIRS, that the environmental education program is designed to be carried out over a period of 20 years (2017 to 2037), with the majority of its activities being directed to the school educational environment and through it to society. Finally, the proposals for environmental education actions for the management of selective household collection projected in the plans and in the program contemplate in part the real need of the population, and they should have more interactive and continuous actions by the institutions that promote selective collection.